The transformation of political parties in a liberal democracy and the voting behavior: Greece 2009-2015 - Νάκας, Αριστείδης (Πανεπιστήμιο Πελοποννήσου, 2016)
The purpose of this research paper is to analyze the transformation of the Greek political parties from a marketing perspective according to the Greek voting behavior, especially after 2009. More specifically, the paper will answer the question “can the voting behavior of Greek people lead to the transformation of the Greek political parties?” The answer is yes, since voters act as consumers and therefore parties need to transform into political organizations. The purposefulness of the research in the academic level is to summarize the existing knowledge in terms of voting behavior and to also constitute an additional pedestal for future research towards this direction. The main contribution of the research, while aspiring to highlight the realistic behavior and reaction of parties, candidates and voters, will be to redefine the existing Greek political structures in order to acquire better policies for society. The methodology of the research is the summoning up of the existing knowledge through literature review, from Google scholar, Greek daily press and the internet, in terms of the keywords above, divided in two chapters, the first being the theoretical background and the second presenting the Greek political system, the paper’s findings, as well as the conclusion.
Η μετεξέλιξη των πολιτικών κομμάτων σε μια φιλελεύθερη δημοκρατία και η συμπεριφορά ψηφοφόρου:Ελλάδα 2009-2015
Keywords: Πολιτικά κόμματα--Ελλάδα; Εκλογές--Ελλάδα; Εκλογική έρευνα; Δημοκρατία--Ελλάδα; Εκλογές--Στατιστική; Δημοκρατία; Πολιτικό σύστημα; Πολιτικά κόμματα; Ελλάδα; Συμπεριφορά ψηφοφόρου